The criminalization of protest in the southern Chile. The landowners from the province of Llanquihue in the Agrarian Reform of the Popular Unity, 1970-1973 - Sánchez Barría, Felipe (Cuadernos de Historia, 2018)
Through unpublished judicial sources, the article describes and analyzes the legal strategies applied by the landowners of the province of Llanquihue to face the implementation of Agrarian Reform (RA) and rural mobilization associated with it, during the government of Popular Unity. It is noted that this strategy was relatively successful, achieving the imprisoning of many rural workers who participating in massive land “seizures” which characterized the period. Also, this legal strategy blocked the expropriation process in this province, provoking conflicts between different branches of the State. Finally, it hopes seeks to show the need to study and understand the locally different dynamics that acquired the conflict associated with RA, especially in southern Chile.